2019
DOI: 10.1021/acscatal.9b01720
|View full text |Cite
|
Sign up to set email alerts
|

Power of the Secondary Sphere: Modulating Hydrogenase Activity in Nickel-Substituted Rubredoxin

Abstract: Secondary sphere interactions are known to significantly impact catalytic rates within biological systems as well as synthetic molecular catalysts. The [NiFe] hydrogenase enzymes oxidize and produce molecular hydrogen at high turnover rates within a complex coordination environment. Nickel-substituted rubredoxin (NiRd) has been developed as a functional, protein-based mimic of the [NiFe] hydrogenase, providing an opportunity to understand the influence of the secondary coordination environment on proton reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 95 publications
0
51
0
Order By: Relevance
“…Based on studies from a series of secondary sphere NiRd mutants it was found that the mutations modulated the activity, H‐bonding network and active site solvent accessibility. The mutant library was made by mutagenesis of three residues in the metal binding loops, Val8, Val34 and Val37.…”
Section: Resultsmentioning
confidence: 99%
“…Based on studies from a series of secondary sphere NiRd mutants it was found that the mutations modulated the activity, H‐bonding network and active site solvent accessibility. The mutant library was made by mutagenesis of three residues in the metal binding loops, Val8, Val34 and Val37.…”
Section: Resultsmentioning
confidence: 99%
“…50 Photocatalytic activity could be achieved and modulated by selective conjugation of a Ru(bpy)3 complex, 51 and detailed spectroscopic and computational characterization of the model elucidated a thiol-inversion mechanism of Ni(III)-hydride formation that is directly applicable to native [NiFe] hydrogenase. 52,53 In addition to mononuclear metalloproteins, heteronuclear bimetallic enzymes have also benefited from replacing the native with non-native metal ions. Despite highly homologous active sites, why a nonheme Cu atom was selected for O 2 reduction in HCO but nonheme Fe was selected for NO reduction in NOR had never been directly probed because removing the nonheme metal ion of either enzyme destabilizes it.…”
Section: Metal Ionsmentioning
confidence: 99%
“…Although most hydrogenase mimicry has focused on the diiron hydrogenase, one of the earliest systems was based on the [NiFe] hydrogenase [155][156][157][158][159][160][161]. Substitution of Ni in rubredoxin yields a catalyst, Ni-Rd, with a tetrathiolate active site mimicking the primary coordination sphere of the Ni site in [NiFe] hydrogenase [155,161].…”
Section: Figmentioning
confidence: 99%
“…A TON greater than 100 (nmol/mg) catalyst was observed, and the biomimetic catalyst is stable through catalysis in aqueous solution, allowing greater than 90% catalyst recovery. The protein structure is amenable to many different mutations, opening the possibility for optimization [160]. In further work, a ruthenium sensitizer was covalently attached to the protein scaffold, creating an integrated hydrogen evolution system [159].…”
Section: Figmentioning
confidence: 99%